(untitled) (International Journal of Food and Nutritional Sciences, 2022)
According to the findings of this research, the significance assigned to legally recognized same-sex marriage by gay, lesbian, bisexual, and transgendered (LGBT) men and women, as well as the effect on their understanding of the LGBT community, is examined. Participants in an open-ended web-based survey (N = 288) were asked to examine the ways in which legalizing same-sex marriage might have a good or negative impact on members of the LGBT community. This study reveals a multilayered understanding of legally recognized same-sex marriage, with an overall theme of equality starting to form a surface over deeper dialogical themes trying to describe tensions in the psychological impact of same-sex getting married on same-sex intimate relationships, on the LGBT community, and on relationships between members of the LGBT community as well as heterosexual people. According to the results of the research, same-sex wedding should be regarded as a framework for any future discussions about married and unmarried same-sex relationships, regardless of their sexual orientation